2014
DOI: 10.1080/17461391.2014.949310
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 fatty acids supplementation improves endothelial function and maximal oxygen uptake in endurance‐trained athletes

Abstract: The study aimed to evaluate the effects of a 3-week n-3 polyunsaturated fatty acids (n-3 PUFA) supplementation on serum nitric oxide (NO), asymmetric dimethyloarginine (ADMA), ultrasound indices of endothelial function and maximal oxygen uptake (VO2 max) of elite cyclists. The effects of dietary supplementation (n-3 PUFA at a dose of 1.3 g twice daily for 3 weeks) and placebo administration on flow-mediated dilatation (FMD), pulse wave velocity, serum markers (NO, ADMA), lipid profile, and ΔVO2max were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 49 publications
3
46
0
2
Order By: Relevance
“…These findings have been supported by recent work demonstrating no effect of n-3 PUFA supplementation on endurance performance or recovery in Australian Rules footballers (treadmill run to exhaustion) [48], well-trained cyclists (cycle to exhaustion) [46] or young healthy people (cycling simulated time trial) [54]. On the other hand, one study did find that n-3 PUFA supplementation (1.1 g/day), versus placebo (lactose monohydrate), resulted in a 3.7 mL kg − 1 min − 1 increase in VO 2max , alongside an increase in endothelial function, although no endurance performance measure was made [56]. Overall, while n-3 PUFA supplementation confers some “beneficial” effects on cardiovascular function, during exercise, this does not translate into an improvement in endurance performance.…”
Section: Endurance Performancementioning
confidence: 99%
“…These findings have been supported by recent work demonstrating no effect of n-3 PUFA supplementation on endurance performance or recovery in Australian Rules footballers (treadmill run to exhaustion) [48], well-trained cyclists (cycle to exhaustion) [46] or young healthy people (cycling simulated time trial) [54]. On the other hand, one study did find that n-3 PUFA supplementation (1.1 g/day), versus placebo (lactose monohydrate), resulted in a 3.7 mL kg − 1 min − 1 increase in VO 2max , alongside an increase in endothelial function, although no endurance performance measure was made [56]. Overall, while n-3 PUFA supplementation confers some “beneficial” effects on cardiovascular function, during exercise, this does not translate into an improvement in endurance performance.…”
Section: Endurance Performancementioning
confidence: 99%
“…Increased shear stress and/or up-regulation of eNOS gene expression enhance vascular NO production and stimulate the regulatory mechanisms of the cardiovascular system [22][23][24], and this effect seems to be enhanced by BPF Gold. Antioxidant administration has been shown to result in dramatic improvements in exercise performance and compelling evidence has been gathered showing the potential ergogenic properties of antioxidants such as NAC [25]. Pertinent to the present study, a series of studies [25] documented signi icant improvements in time to fatigue during high intensity cycling.…”
Section: Discussionmentioning
confidence: 71%
“…Antioxidant administration has been shown to result in dramatic improvements in exercise performance and compelling evidence has been gathered showing the potential ergogenic properties of antioxidants such as NAC [25]. Pertinent to the present study, a series of studies [25] documented signi icant improvements in time to fatigue during high intensity cycling. The mechanisms responsible for the improved performance may be associated with increased antioxidant availability and improved K + regulation as a result of maintained Na + /K + pump.…”
Section: Discussionmentioning
confidence: 71%
“…Ten studies showed significantly improved endothelial vasodilator function (three within treatment group, and seven compared to placebo) after LCn-3 PUFA supplementation [23,24,25,26,27,28,29,30,31,32] (Table 1). For the statistical analysis, four studies were excluded because baseline FMD was not reported (analyzed: n = 14) [24,25,33,34].…”
Section: Effects Of Lcn-3 Pufa Supplementation On Endothelial Vasomentioning
confidence: 99%